An investigation into the pharmacological properties of propolis - Hu, Fuliang (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
Propolis is a traditional value-added product from beekeeping, and has been widely used in medicine and the chemical industry because of its extensive biological activities. In this dissertation some pharmacological properties of propolis extracted by ethanol (EEP) and water (WSP) were studied by means of modem pharmacological methods. The results of the experiments show the following: 1. Both EEP and WSD led to decreased levels of fasting blood glucose (FBG), glycosylated haemoglobin (HBA1c), Fructosamine (FRU), blood urea nitrogen (BUN), uric acid (UA), malonaldehyde (MDA), nitric oxide (NO), nitric oxide synthetase (NOS), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) and very-low density lipoprotein cholesterol (VLDL-C) in the serum of fasting rats; and, to increased serum levels of high-density lipoprotein cholesterol (HDL-C) and superoxide dismutase (SOD) in rats with diabetes mellitus. This suggests that propolis can control blood glucose and modulate the metabolism of glucose, blood lipid and protein, leading to decreased outputs of lipid peroxidation and scavenging free radicals in rats with diabetes mellitus. 2. Both EEP and WSD showed inhibitory effects on swelling induced by Freund's complete adjuvant and decreased the degree of local inflammatory responses; significantly inhibited the increase of interleukin-6 (lL-6) in inflamed tissues, but had no significant effect on levels of interleukin-2 (IL-2) and interferon-y (IFN-y). The results are consistent with the interpretation that EEP and WSD may exert these effects by inhibiting the activation and differentiation of mononuclear macrophages. 3. Both EEP and WSD exhibited significant anti-inflammatory effects in animal models with respect to thoracic capillary vessel leakage in mice, Carrageenan-induced oedema, Carrageen-aninduced pleurisy and acute lung damage in rats. The mechanisms for the anti-inflammatory effects probably involve decreasing prostaglandin and NO levels. 4. Both EEP and WSD had an inhibitory effect on the level of TG, TC, LDL-C, glutamic-pyruvic transaminase (GPT) and glutamic-oxalacetic transaminase (GOT) in serum, and TC, TG and MDA in liver of hyperlipidemic SD rats; but were without effects on HDL-C, MDA, SOD and NO in serum. EEP also reduced body weight, liver weight and liver index, but WSD did not reduce those indexes. The results showed that the two extracts contribute to the improvement of lipid metabolism in hyperlipidemic rats and provide them with the required anti-oxidative activity. 5. The 80% ethanol extracts of propolis had the highest flavonoid content. The flavone content of water extracts of propolis were obtained with a natural surface-active agent, under ultrasonic perturbation at 80Â°C, for 12 h and was 6.7 times greater than that of propolis extracted with water at room temperature. Compared to EEP, WSD has the same or a greater anti-tumor or anti-inflammation effect at the same dosage, and shows considerable pharmacological potential especially because of its low side effects and ease of preparation.
Keywords: Propolis